Managing complications of radiation therapy in head and neck cancer patients: part VI. management of opportunistic infections - Ngeow, Wei Cheong; Chai, Wen Lin; Ramli, Roszalina; Rahman, Roslan Abdul (World Scientific Publishing, 2006)
Head and neck cancer is becoming a more recognizable pathology to the general population and dentists. The modes of treatment include surgery and/or radiation therapy. Where possible, pretreatment dental assessment shall be provided for these patients before they undergo radiation therapy. There are occasions, however, whereby head and neck cancer patients are not prepared optimally for radiation therapy. Because of this, they succumb to complicated oral adverse effects after radiation therapy. The last part of this series reviews the opportunistic infections that can occur to the perioral structure. Their management is briefly discussed. Â© 2006 Elsevier. All rights reserved.